Strategies for Efficient Gene Editing in Protoplasts of Solanum tuberosum Theme: Determining gRNA Efficiency Design by Utilizing Protoplast (Research) - Carlsen, Frida Meijer; Johansen, Ida Elisabeth; Yang, Zhang; Liu, Ying; Westberg, Ida Nøhr; Kieu, Nam Phuong; Jørgensen, Bodil; Lenman, Marit; Andreasson, Erik; Nielsen, Kåre Lehmann; Blennow, Andreas; Petersen, Bent Larsen (Frontiers in Genome Editing, 2022)
Potato, Solanum tuberosum is a highly diverse tetraploid crop. Elite cultivars are extremely heterozygous with a high prevalence of small length polymorphisms (indels) and single nucleotide polymorphisms (SNPs) within and between cultivars, which must be considered in CRISPR-Cas gene editing strategies and designs to obtain successful gene editing. In the present study, in-depth sequencing of the gene encoding glucan water dikinase (GWD) 1 and the downy mildew resistant 6 (DMR6-1) genes in the potato cultivars Saturna and Wotan, respectively, revealed both indels and a 1.3-2.8 higher SNP prevalence when compared to the heterozygous diploid RH genome sequence as expected for a tetraploid compared to a diploid. This complicates guide RNA (gRNA) and diagnostic PCR designs. At the same time, high editing efficiencies at the cell pool (protoplast) level are pivotal for achieving full allelic knock-out in tetraploids. Furthermore, high editing efficiencies reduce the downstream cumbersome and delicate ex-plant regeneration. Here, CRISPR/Cas ribonucleoprotein particles (RNPs) were delivered transiently to protoplasts by polyethylene glycol (PEG) mediated transformation. For each of GWD1 and the DMR6-1, 6-10 gRNAs were designed to target regions comprising the 5’ and the 3’ end of the two genes. Similar to other studies including several organisms, editing efficiency of the individual RNPs varied significantly, and some generated specific indel patterns. RNP’s targeting the 5’ end of GWD1 yielded significantly higher editing efficacy as compared to targeting the 3’ end. For DMR6-1, such an effect was not seen. Simultaneously targeting each of the two target regions with two RNPs (multiplexing) yielded a clear positive synergistic effect on the total editing when targeting the 3’ end of the GWD1 gene only. Multiplexing of the two genes, residing on different chromosomes, yielded no or a slightly negative effect on editing from the single or combined gRNA/RNPs. These initial findings may instigate much larger studies needed for facilitating and optimizing precision breeding in plants.